2016
DOI: 10.26881/ae.2016.13.06
|View full text |Cite
|
Sign up to set email alerts
|

Artysta bez skrzydeł? Regulacja emocji poprzez doświadczenia estetyczne

Abstract: Sztuka może pomagać radzić sobie z trudnymi doświadczeniami. Sesje arteterapii (leczenia poprzez sztukę) są znanym i skutecznym rodzajem terapii. Jednocześnie obserwuje się tendencje do – wydawać by się mogło – nieefektywnego dla dobrostanu (emocji, nastroju) angażowania się w tworzenie bądź kontakt ze sztuką (na przykład słuchanie smutnych piosenek, ekspresywne pisanie o trudnych przeżyciach). Wielu autorów opisywało, jak regulujemy negatywne emocje. Treści te nie wyczerpywały jednak tematu w odniesieniu do s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…According to Granot et al (2021) , there are many purposes of listening to music, e.g., experiencing aesthetic pleasure, determining one’s own identity, bringing back memories or changing one’s own mood. Osowiecka and Gacka (2016) write that while creating music presenting hardships (e.g., hip hop brings up the topics of addictions and poverty), performers cope in this way with problems and give listeners hope for a better future. Furthermore, they refer to the work of Van den Tol and Edwards (2015) , who believe that the identification with emotions from a song allows listeners to re-experience something, the experience of connecting with the message of the song may motivate them to be active (undertake actions), the aesthetic value may divert their attention from problems, and memories evoked by the piece of music allow them to experience them again and see them in a new light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Granot et al (2021) , there are many purposes of listening to music, e.g., experiencing aesthetic pleasure, determining one’s own identity, bringing back memories or changing one’s own mood. Osowiecka and Gacka (2016) write that while creating music presenting hardships (e.g., hip hop brings up the topics of addictions and poverty), performers cope in this way with problems and give listeners hope for a better future. Furthermore, they refer to the work of Van den Tol and Edwards (2015) , who believe that the identification with emotions from a song allows listeners to re-experience something, the experience of connecting with the message of the song may motivate them to be active (undertake actions), the aesthetic value may divert their attention from problems, and memories evoked by the piece of music allow them to experience them again and see them in a new light.…”
Section: Introductionmentioning
confidence: 99%
“… Fancourt et al (2020) showed in their studies that training in doing an artistic activity, regular engagement in the production of art, and enjoyment while engaging are all associated with a greater ability to use artistic activities to regulate our emotions. Osowiecka and Gacka (2016 , p. 69) write that “most artists are convinced (and certainly they have such a feeling) that they create to experience emotional well-being” and they draw attention to the human need to create art even in extremely unfavorable conditions, e.g., by concentration camp prisoners or political prisoners. Based on the above intuitions, it was assumed that:…”
Section: Introductionmentioning
confidence: 99%